Warehouse Management Using Economic Order Quantity - Kumklong, Napassawan; Hotrawaisaya, Chattrarat (Journal of Innovation and Management, 2020)
The objective of this study was to study the quantity and quantity of raw material purchase orders. The order of the customer by the information of the order of raw materials in 2016 is used to analyze the total value of purchased raw materials by grouping inventory to select the most important inventory or Group A, which will be valued at 70% to 80% of the value. All raw materials and raw materials that are important to them are Group B, which is valued at around 20% to 30% of the total value of raw materials. The theoretical calculation of the size of the order for a Dutch model. Normally, to find the value of order quantity, save size and compare the total cost with the form of Traditional Procurement The results show that total cost of inventory of Group A total 5 items have total cost. When comparing traditional procurement and new procurement, it was found that the total cost of raw materials was 64,502 baht per year, while Group B cost of raw materials It can be reduced to 105,835 baht per year, which is included Total inventory can reduce capital to 125,978 baht per year.